COVID 19 and mask in sports - Pifarré, F.; Dulanto Zabala, D.; Grazioli, G.; de Yzaguirre i Maura, I. (Apunts Sports Medicine, 2020)
Introduction: Due to the mandatory use of a mask, and the authorization to do outdoor sports in Catalonia, we try to assess the physiological impact of the hypercapnia hypoxia generated by the masks during aerobic sports practice.